Russian Accounting Society of Mutual Assistance. History of the Academic Society of Accountants - Sokolov, Viatcheslav; Karelskaia, Svetlana; Zuga, Ekaterina (De Computis, Revista Española de Historia de la Contabilidad., 2023)
This research deals with the activities of the Russian Accounting Society of Mutual Assistance founded in 1907 in St. Petersburg by a group of accounting teachers led by E. Sievers. We have described the spheres of activity of the society as well as its peculiarities in comparison with other accounting societies at the beginning of the 20th century. The article includes the biography of the Society’s founder, Evstafiy Sievers (1852-1917), the Society's structure, membership policy (it was one of the first Russian accounting societies to admit women), scientific activities, including Sievers’ theory of exchange and analysis of publications in the journal “Business Education”, as well as analysis of the society’s influence on the development of accounting in Russia. Links with other Russian accountants’ societies are described. The research results contribute to the history of the development of non-professional accounting societies and to the history of the development of accounting theory and education in Russia.